2149. Real-Time Nationwide Surveillance for Antimicrobial Resistance of Major Pathogens Using Automated Data Collection System in Korea: A KARS-Net Study. (26th November 2018) - Huh, Kyungmin; Ha, Young Eun; Chung, Doo Ryeon; Ko, Jae-Hoon; Kim, Hyunsoo; Yong, Dongeun; Lee, Kyungwon; Huh, Hee Jae; Lee, Nam Yong; Oh, Suhyun; Jang, Sukbin; Mun, Seokjun; et al.
Abstract: Background: Information on the most current status of antimicrobial resistance (AMR) in local and national levels has critical importance. However, collection and analysis of a large number of antimicrobial susceptibility test (AST) results often results in additional workload in healthcare facilities and latency in final reporting. We sought to develop an automated nationwide surveillance network in Korea. Methods: Data collection servers were set up at each participating institutions, which collects AST results of every bacterial isolate from blood, cerebrospinal fluids, urine, and respiratory specimens. Collected results are anonymized and transmitted to central data server every day without human input. End-user can perform various analyses using data warehouse server through web interface. Only first isolates of same species from individual patients were included in analysis. Results: A total of 19 hospitals located in various regions in Korea participated to the network. From January 2015 through December 2017, AST results of 347, 356 isolates were collected. The proportion of MRSA among S. aureus ( n = 17, 761) was 65.3%, which declined gradually from 71.5 to 62.3% during study period ( P < 0.001). The proportion of VRE increased from 29.3 to 36.3% ( P = 0.001). Resistance rates of E. coli ( n = 63, 628) to third and fourth generation cephalosporins, fluoroquinolone, and piperacillin–tazobactam were 31.6, 23.0, 44.0, and 4.2%, respectively. Resistance rates of K. pneumoniae ( n = 16, 875) to same classes were 32.2, 28.1, 31.0 and 19.1%, respectively. Among E. coli and K. pneumoniae, 0.4 and 4.3% were resistant to carbapenem. Resistance rates of P. aeruginosa ( n = 12, 895) to carbapenem was 30.5%. However, 72.7% of A. baumannii isolates ( n = 9, 885) were resistant to carbapenem. Colistin resistance rate was still low at 0.5%. Conclusion: We have established a fully automated nationwide surveillance network for AMR in Korea. Our system provided data on the most current status of AMR, which revealed increase in resistance rates among major Gram-negative pathogens compared with previous studies. Disclosures: All authors: No reported disclosures.